1998
DOI: 10.1056/nejm199801153380302
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Weight and the Risk of Adverse Pregnancy Outcomes

Abstract: Higher maternal weight before pregnancy increases the risk of late fetal death, although it protects against the delivery of a small-for-gestational-age infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

49
559
9
54

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 949 publications
(680 citation statements)
references
References 22 publications
49
559
9
54
Order By: Relevance
“…36,37 The slow growth-and accelerated growth-related adverse health outcomes in later life may represent different disease mechanisms, and both may be modified by growth during infancy and childhood. 32,35,38 Therefore, the significance of macrosomia is not just for its relationship with short-term outcomes such as prolonged labor, cesarean section, and birth injury. The possibility of increased risk on long-term health outcomes, such as obesity, in childhood and adulthood of macrosomia should be considered as well.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 The slow growth-and accelerated growth-related adverse health outcomes in later life may represent different disease mechanisms, and both may be modified by growth during infancy and childhood. 32,35,38 Therefore, the significance of macrosomia is not just for its relationship with short-term outcomes such as prolonged labor, cesarean section, and birth injury. The possibility of increased risk on long-term health outcomes, such as obesity, in childhood and adulthood of macrosomia should be considered as well.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with a doubling in risk of late fetal death in parous women. 28 Also, some study results have suggested that obese women are at increased risk of caesarean section, 29 although results are inconsistent. 30 Our results might be accounted for by a confounding effect of obesity, but this is unlikely for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the association between previous caesarean birth and stillbirth was stronger than that described for a body-mass index greater than 30. 28 Moreover, if the excess of antepartum stillbirths in the previous caesarean delivery group was caused by a confounding effect of a known risk factor, it was not being addressed; these deaths occurred at term, when elective caesarean delivery has little risk of neonatal death. 7 Although the association between previous caesarean delivery and the risk of unexplained stillbirth is unlikely to be due to an unmeasured confounder, we cannot exclude this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be an upward trend [2,3], which contributes to almost 3.6 million preterm births accounting for 23.6% of the global preterm births reported each year [4]. Preterm birth has been consistently associated with maternal underweight and nutrient deficiencies during pregnancy [5][6][7][8][9]. Therefore, nutritional assessment needs to be an integral part of antenatal care and should be continued during pregnancy in order to reduce the risk of maternal, fetal and neonatal complications, as well as the short-and long-term adverse outcomes.…”
mentioning
confidence: 99%